Postpartum Blues - Husband's Support for Primipara Birth: Scoping Review - Gemi Rahayu (Indonesian Journal of Global Health Research, 2025)
The process of childbirth causes several psychological changes in the mother, feelings of happiness, sadness and fear. These changes in feelings can occur in the first week after giving birth. Postpartum psychological changes called postpartum blues are more at risk of occurring in primitive mothers, where there is a change in the role of a mother. Husband's support greatly affects how psychological changes can cause postpartum blues problems especially in primitive mothers. The purpose of this literature review study was made to identify the husband's support for the incidence of baby blues in primipara mothers. The method used in this study is a socpong review and was systematically studied based on PRISMA flow cahart using Proquest, ScienceDirect, and Google Scholar databases with the keywords "husband support" and "primipara". With the inclusion criterion, research articles in 2017-2022 were found 871 articles using English, full text and in the form of articles. After scanning, 16 articles were obtained that matched the criteria and then a review was carried out. The results of the scoping review study showed that the husband's support for primipara mothers showed that mothers who received support from their husbands were less at risk of experiencing postpartum blue.